Disability standards and inclusiveness in education: a review of the Australian landscape - Guthrie, Rob; Waldeck, Elizabeth (A B Academic Publishers, 2008)
This paper examines the potential effects of the Disability Standards for Education 2005 (the Education Standards) on Australian education providers by considering the growth of inclusiveness in Australian education and the effects of the High Court decision in Purvis v. State of New South Wales. The paper observes that the decision in Purvis was a setback for the process of inclusiveness, which has since been addressed to a large extent by the introduction of the Education Standards. In addition, the paper considers the United States experience in relation to inclusiveness in education. It notes that the legislative underpinning of the principle in that jurisdiction has lead to inconsistent approaches by the courts in applying the objectives of inclusiveness. The paper concludes with reflections on whether the Australian approach has converged with the United States experience.